CHIEF OFFICE AND COUNCIL OF THE CAUCASIAN VICEROY (1858): BACKGROUND OF FORMATION, STRUCTURE AND SCOPE OF THEIR POWERS - ABAZOV, A.H. (Kavkazologiya, 2019)
The article considers the prerequisites for the creation, the structure and scope of powers of the Head department and the Council of the Caucasian Viceroy. The Regulation «On the Chief Office and Council of the Caucasian Viceroy» adopted on December 21, 1858 was analyzed in detail. It is noted that as the administrative and territorial changes in the region were carried out in the 40-50-s of the XIX century, the need to review the existing and adopt new normative acts regulating the activities of administrative structures in the region increased. The correspondence of the Caucasian Viceroy A.I. Baryatinsky with the heads of the highest authorities of the Russian Empire, which discussed the necessity and validity of this transformation, is analyzed. The structure and powers of the relevant departments (general affairs, court cases, financial and state property), the Department of Agriculture and Colonies of Foreign Settlers in the Caucasus and behind the Caucasus, the archive, the treasury, the register, the printing house, the public library and the editorial office of the newspaper Caucasus and the Transcaucasian Gazette were considered. The staff table of the General Directorate of the Mayor of the Caucasus for 1859-1860 was analyzed. It is concluded that during the administrative reforms in 1858 an administrative institution was established under the Caucasian Viceroy, to exercise his powers as a senior official in the province, to determine the main directions of development and development of the Caucasus region, to ensure the implementation of the orders of the Emperor and the highest bodies of state power of the Russian Empire.